2002
DOI: 10.1080/03050620213653
|View full text |Cite
|
Sign up to set email alerts
|

Alliance Treaty Obligations and Provisions, 1815-1944

Abstract: This article introduces the Alliance Treaty Obligations and Provisions (ATOP) dataset. We begin by describing the rationale for collecting the ATOP data, its scope, and some general coding rules for the project. Then we offer some descriptive statistics for phase one of the dataset, which covers the years 1815-1944, and reveal some interesting trends in alliance politics. Finally, we replicate a study of alliance formation originally conducted by Lai and Reiter (2000) to demonstrate the effect the use of ATOP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
388
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 570 publications
(409 citation statements)
references
References 15 publications
5
388
0
2
Order By: Relevance
“…Recorded as 1 if the primary sender and the target are formally allied (Leeds, Ritter, Mitchell, and Long 2002). …”
Section: Allymentioning
confidence: 99%
“…Recorded as 1 if the primary sender and the target are formally allied (Leeds, Ritter, Mitchell, and Long 2002). …”
Section: Allymentioning
confidence: 99%
“…One such factor that could be easily explored was the overall dissimilarity between the regimes of both states within a dyad, because -as noted above -previous studies have shown that this factor tends to have an exacerbating impact on conflicts (Souva 2004). 26 Accordingly, states may perceive a competitor as more or less threatening depending on how different the regimes of both 25 See Leeds et al (2002) for a description of this dataset. All data and codebooks are available online at:…”
Section: Operationalization and Methodologymentioning
confidence: 99%
“…I use the population of cases provided by Leeds (2003), which is based on the Alliance Treaty Obligations and Provisions (ATOP) data set (Leeds et al, 2002). The version of the data used here contains 143 cases spanning from 1816 to 1944 and is directed, such that each case refers to one member of an alliance at a point in time in which the terms of the alliance are called into effect (what Leeds calls 'war performance opportunities') (Leeds, 2003, pp.…”
Section: Dependent Variable: Alliance Violationmentioning
confidence: 99%
“…Alliances involve costs for all members and thus are not likely to be entered into lightly, and yet the existence of alliance violations in world history is indisputable. Formal theoretical work on alliances by Smith (1995Smith ( , 1996, Morrow (1994) and Fearon (1997) offers models that expect no violation of alliances or very infrequent violation of alliances, even though empirical work has established that formal alliances are violated approximately 25 percent of the time (Leeds et al, 2002).…”
Section: Introductionmentioning
confidence: 99%